2021
DOI: 10.1108/apjml-04-2020-0204
|View full text |Cite
|
Sign up to set email alerts
|

Examining the impact of external reference prices on seller price image dimensions and purchase intentions in pay what you want (PWYW)

Abstract: PurposePay what you want (PWYW) is a participative pricing mechanism that permits customers complete freedom to choose prices. PWYW literature reports the influence of external reference price (ERP) on customers' price decisions and payments. The current research examines the influence of ERP presence, salience and understanding at the seller level by analysing customers' perceptions of seller price image dimensions and purchase intentions.Design/methodology/approachStudy 1 tests the impact of ERP presence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 96 publications
2
4
0
2
Order By: Relevance
“…Furthermore, similar results concerning the relationship between perceived price and consumers' purchase intention were also generated within the results performed by Weisstein et al, (2014), Lee and Stoel (2014), Rai andNarwal (2021), andNisar et al, (2020), in which, these studies also found the significant impact given by perceived price toward consumers' purchase intention. Therefore, based on these explanations and arguments based on several previous studies, authors would like to propose the following hypothesis:…”
Section: H1: Attitude Toward the Behavior Had A Significant Effect To...supporting
confidence: 82%
“…Furthermore, similar results concerning the relationship between perceived price and consumers' purchase intention were also generated within the results performed by Weisstein et al, (2014), Lee and Stoel (2014), Rai andNarwal (2021), andNisar et al, (2020), in which, these studies also found the significant impact given by perceived price toward consumers' purchase intention. Therefore, based on these explanations and arguments based on several previous studies, authors would like to propose the following hypothesis:…”
Section: H1: Attitude Toward the Behavior Had A Significant Effect To...supporting
confidence: 82%
“…This research contributes to the existing literature in several ways. Firstly, the findings demonstrate that in the operation of two-sided media platforms, formulating reasonable payment schemes is an effective measure alongside discriminatory pricing (Lin, 2020), reference prices (Rai and Narwal, 2022), and subsidies (Li and Zhang, 2020). The introduction of the first-enjoy-after-pay service can effectively attract users by influencing their willingness to pay and subscription behavior based on the order of paying membership fees and enjoying membership benefits.…”
Section: Discussionmentioning
confidence: 97%
“…Narwal and Nayak (2020) studied the benefits of PWYW as a novel strategy for price discrimination in multi-channel retailing environment. In sum, the literature shows that under PWYW, consumers are economically rational, care for their social image and are motivated by fairness and reciprocity concerns while paying for the product/service they received (Narwal et al, 2021;Rai and Narwal, 2022).…”
Section: Pay-what-you-want (Pwyw) Pricingmentioning
confidence: 99%
“…In sum, the literature shows that under PWYW, consumers are economically rational, care for their social image and are motivated by fairness and reciprocity concerns while paying for the product/service they received (Narwal et al. , 2021; Rai and Narwal, 2022). Table 1 lists all the factors supporting PWYW implementation.…”
Section: Literature Reviewmentioning
confidence: 99%